2021
DOI: 10.1109/tse.2019.2901679
|View full text |Cite
|
Sign up to set email alerts
|

Rebooting Research on Detecting Repackaged Android Apps: Literature Review and Benchmark

Abstract: Repackaging is a serious threat to the Android ecosystem as it deprives app developers of their benefits, contributes to spreading malware on users' devices, and increases the workload of market maintainers. In the space of six years, the research around this specific issue has produced 57 approaches which do not readily scale to millions of apps or are only evaluated on private datasets without, in general, tool support available to the community. Through a systematic literature review of the subject, we argu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 89 publications
0
69
0
Order By: Relevance
“…The purpose of data collection was to observe user decisions for learning their permission expectations against given functions. These data would help us determine the gap among user expectations and the actual permission requirements of GA. We determined this gap by analyzing the responses to learn their similarities with the permission requirements of GA. To achieve this, we calculated Jaccard similarity among the responses and the actual permission requirements of GA. Jaccard similarity has been used in research addressing decision-making issues, and discovering harmful behaviors of Android apps [70][71][72]. Measuring the Jaccard similarity coefficient j between two datasets A and B is the result of the division between the number of features that are common to all divided by the total number of properties [73].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of data collection was to observe user decisions for learning their permission expectations against given functions. These data would help us determine the gap among user expectations and the actual permission requirements of GA. We determined this gap by analyzing the responses to learn their similarities with the permission requirements of GA. To achieve this, we calculated Jaccard similarity among the responses and the actual permission requirements of GA. Jaccard similarity has been used in research addressing decision-making issues, and discovering harmful behaviors of Android apps [70][71][72]. Measuring the Jaccard similarity coefficient j between two datasets A and B is the result of the division between the number of features that are common to all divided by the total number of properties [73].…”
Section: Discussionmentioning
confidence: 99%
“…Static analysis has been also a popular technique to dissect Android apps [23,24,38,41]. For example, researchers have used static taint analysis to discovery privacy leaks in Android apps [4] and leveraged model checking techniques to verify Android apps in terms of their security properties [6].…”
Section: Related Workmentioning
confidence: 99%
“…More recently, Nguyen et al [15] demonstrated the complete ineffectiveness of commercial and open-source anti-virus Android apps in detecting a malicious repackaged application (Snapchatz). Li et al [16] in a 2019 survey-based study also highlighted the shutdown by federal authorities of alternative Android market places because of app plagiarism (repackaging or cloning) [17]. The same survey [16] also recounted reports by Ustwo Games that only 5% of the Android installations for one of its more popular games were legitimate (as in paid for, and not repackaged or cloned).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [16] in a 2019 survey-based study also highlighted the shutdown by federal authorities of alternative Android market places because of app plagiarism (repackaging or cloning) [17]. The same survey [16] also recounted reports by Ustwo Games that only 5% of the Android installations for one of its more popular games were legitimate (as in paid for, and not repackaged or cloned).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation